2004
DOI: 10.1002/meet.1450410142
|View full text |Cite
|
Sign up to set email alerts
|

Free sorting of images: Attributes used for categorization

Abstract: Categorization is crucial to human perception and cognition. Without the abilities to categorize, people would not be able to deal with the multitude of things they perceive daily. Past research has shown that categorization also facilitates effective and efficient browsing of both text and image documents especially when users have no specific document in mind but only some idea of what they are looking for. However, the question of what types of attributes should be used to index categorieslgroupings of imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…This is consistent with the results from several earlier studies (Fidel, 1997;Greisdorf & O'Connor, 2002;Jörgensen, 1998;Jörgensen, 1999;Mojsilovic & Rogowitz, 2001a;Rorissa & Hastings, 2004). High-level and affective concepts were also used in image categorization while some but relatively few categories were based on similar visual elements.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This is consistent with the results from several earlier studies (Fidel, 1997;Greisdorf & O'Connor, 2002;Jörgensen, 1998;Jörgensen, 1999;Mojsilovic & Rogowitz, 2001a;Rorissa & Hastings, 2004). High-level and affective concepts were also used in image categorization while some but relatively few categories were based on similar visual elements.…”
Section: Discussionsupporting
confidence: 91%
“…The affective responses to images and the atmosphere of the image itself have been deemed important in the selection process of journalistic photographs (Kobré, 2000;Markkula & Sormunen, 1998) and based on these categorization results they also seem to be a natural way for people to organize photographs. The influence of the photographs' emotional tone on categorization has not been discussed much in previous studies, although the image categories reported by Rorissa and Hastings (2004) included several affective themes. Other studies on free categorization (Vailaya et al, 1998;Teeselink et al, 2000) seem to concentrate purely on the generic semantic level of image content (justified because of their interest in, for example, automatic image classification), whereas several of the journalistic photographs used in this study contained affective subject matter.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations